1996
DOI: 10.1177/140349489602400407
|View full text |Cite
|
Sign up to set email alerts
|

National health insurance consumption and chronic symptoms following mild neck sprain injuries in car collisions

Abstract: Many reported sustained symptoms after neck sprain injuries, 16% of them reported being in a bad state of health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0
2

Year Published

1999
1999
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(28 citation statements)
references
References 8 publications
2
24
0
2
Order By: Relevance
“…These results are similar to those reported in Norway, where 31% of subjects with chronic neck/shoulder pain due to tra¤c collisions were not working full-time three to eight years after the collision (41). In our study, we had expected a larger proportion of disabled workers in 1994, since this year was a part of an economic recession in Sweden, while the economy was much better in 1989.…”
Section: Work Disabilitysupporting
confidence: 93%
“…These results are similar to those reported in Norway, where 31% of subjects with chronic neck/shoulder pain due to tra¤c collisions were not working full-time three to eight years after the collision (41). In our study, we had expected a larger proportion of disabled workers in 1994, since this year was a part of an economic recession in Sweden, while the economy was much better in 1989.…”
Section: Work Disabilitysupporting
confidence: 93%
“…Differing recruitment methods likely explain the differences, and our lower figures [29]. Borchgrevink et al, in an ED-based study, found that 27% of 426 patients had been on sick leave, while Karlsborg et al reported a median absence from work of six days (0 days-9 months) [30,31]. Those two studies also included short-term sick leave of less than two weeks, making direct comparison with our figures difficult.…”
Section: Discussionmentioning
confidence: 64%
“…Overall, 34% complained of neck discomfort during or after carrying out normal everyday tasks. 23 Patients with degenerative disease may tend to be older and have more symptoms than those with normal radiographs at the time of injury, 24,25 although this is not certain within the existing literature. 26,27 If WAD solely resulted from a pathologic physical lesion, it could be reasonably expected that this would be more marked in the victims of high-energy trauma.…”
Section: Discussionmentioning
confidence: 97%